Assessment of Sewage Molecular Markers in Port Dickson Coast and Kim Kim River with Sediment Linear Alkylbenzenes - Sadeq Abdullah Abdo Alkhadher, Sadeq Abdullah Abdo Alkhadher; Zakaria, Mohamad Pauzi; Suratman, Suhaimi; Tahani Y. A. Alanazi, Tahani Y. A. Alanazi; A. H. Al-Bagawi, A. H. Al-Bagawi; Sami M. Magam, Sami M. Magam; Najat Masood, Najat Masood; Abdul Kadir, Aeslina; Adel Al-Gheethi, Adel Al-Gheethi (Taylor&francis, 2022)
The present study aimed to determine linear alkylbenzenes (LABs) concentrations as organic molecular marker for sewage pollution in the sediment samples collected from Coast of Port Dickson and Kim Kim River, Peninsular Malaysia. The adverse effects of anthropogenic inputs into the rivers and coastal environment could be detected by molecular organic markers such as LABs. The sediments were processed; their sources were identified and tested by gas chromatography-mass spectrometry (GC-MS). The significance of the differences among sampling stations for LAB concentrations and distribution at p < 0.05 was performed by analysis of variance and Post Hoc Tests, LSD procedures (ANOVA) and Pearson correlation coefficient. LABs indices which include internal to external (I/E) congeners, long to short chains L/S and homologs C13/C12 were used to identify the sewage treatment and degradation levels. Results of this study are statistically uncovered that the range of RLABs concentration in the investigated locations was between 112.0; 88.3 and 256.0; 119.0 ngg1 dw, respectively. There was significant difference (p < 0.05) of LAB homologs with high percentage of C13-LAB homologs along sampling locations. The calculated LAB ratios (I/E) were within the range between 2.0; 1.7 and 4.1, 2.0, demonstrated that, the treated effluents from primary and secondary sources were discharged to the study areas. The degradation of LABs was 40–64% and 34–38% in the studied locations. The findings of this study suggested the powerfully indicators of LABs in tracing anthropogenic sewage contamination and the necessity of continuing wastewater treatment system improvement